Challenges to the Accounting Profession. - Mautz, R. K. (The Accounting Review, 1965)
This article discusses the challenges to the accounting profession. Accounting education is under pressure from a number of directions. It is caught in the current criticism of all undergraduate schools of business that education for business generally is not sufficiently rigorous, that it has neglected the basic disciplines, that it is too specialized, that it emphasizes procedures and descriptions rather than being analytical in nature, and that all in all it has forsaken the liberal approach and ought to be revised substantially. Professional accountants question accounting education on other grounds. They continually seek not only professionally oriented programs but professional stature as well and are concerned lest the absence of professional schools have undesirable implications, both educationally and prestige-wise. From the functional fields of business, which are agreed that all students of business should have some acquaintance with accounting, one receives complaints that the elementary courses are intended primarily for accounting majors and fail to give non-accounting majors the kind of familiarity with accounting that they need for their purposes.